Atmospheric Basins: Identification of Quasi‐Independent Spatial Patterns in the Global Atmospheric Hydrological Cycle Via a Complex Network Approach. Issue 22 (22nd November 2020) - Zhang, Yu; Huang, Wenyu; Zhang, Mingxi; Tian, Yinglin; Wang, Guangqian; Zhong, Deyu
Abstract: A river basin is commonly assumed to be a closed unit of the terrestrial hydrological cycle. Further research is required to identify analogous regional‐scale and quasi‐independent spatial patterns with the potential to be treated as basic hydrological units of the atmospheric hydrological cycle. To this purpose, we constructed global atmospheric moisture networks (GAMNs) for the boreal summers and winters from 2007 to 2016 based on the atmospheric source‐sink relationships between grid cells of a global 3° × 3° grid generated by the Eulerian atmospheric moisture tracking model WAM‐2layers (water accounting model‐two layers). By adopting a complex network‐based approach, we identified regional‐scale patterns in the GAMNs that reflect the regional moisture transport characteristics and have high moisture recycling ratios (>50%) and defined these patterns as atmospheric basins. Moisture exchanges between atmospheric basins are non‐negligible, and several atmospheric basins act as strong moisture providers/receivers. Moreover, typical atmospheric basins were selected to check the stability and variation of atmospheric basins during 2007–2016. We observed core regions that persist throughout the years in these atmospheric basins. Inter‐annual differences in the positions and areas of these atmospheric basins were also observed, and we attributed these to inter‐annual differences in the atmospheric moisture links. Identifying atmospheric basins can help to better understand the global hydrological cycle dynamics and drivers as it reduces the complexity of the grid‐based source‐sink relationships of atmospheric moisture. Key Points: We identified regional‐scale patterns with high moisture recycling ratios (>50%) and defined them as atmospheric basins We constructed global networks of atmospheric basins and quantified their moisture flows Atmospheric basins have core regions that persist throughout 2007–2016, and inter‐annual differences in their positions can be observed